2015
DOI: 10.3324/haematol.2015.128553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term outcomes between children with aplastic anemia and refractory cytopenia of childhood who received immunosuppressive therapy with antithymocyte globulin and cyclosporine

Abstract: The 2008 World Health Organization classification proposed a new entity in childhood myelodysplastic syndrome, refractory cytopenia of childhood. However, it is unclear whether this morphological classification reflects clinical outcomes. We retrospectively reviewed bone marrow morphology in 186 children (median age 8 years; range 1-16 years) who were enrolled in the prospective study and received horse antithymocyte globulin and cyclosporine between July 1999 and November 2008. The median follow-up period was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
(20 reference statements)
2
19
0
Order By: Relevance
“…However, 19% developed cytogenetic abnormalities including -7, a poor prognosis finding(25). These results are similar to the observation that G-CSF treatment concurrent with IST increased the risk of development of -7 abnormalities and progression to MDS/AML(2628). …”
Section: Cytogenetic Abnormalities After Treatment With Tpo-mimeticssupporting
confidence: 89%
“…However, 19% developed cytogenetic abnormalities including -7, a poor prognosis finding(25). These results are similar to the observation that G-CSF treatment concurrent with IST increased the risk of development of -7 abnormalities and progression to MDS/AML(2628). …”
Section: Cytogenetic Abnormalities After Treatment With Tpo-mimeticssupporting
confidence: 89%
“…While there is no evidence that granulocyte colony stimulating factor (G-CSF) potentiates transformation to MDS or changes overall survival in AA (Teramura, et al 2007, Tichelli, et al 2011), this may be a reflection of the relatively short duration of G-CSF therapy given to most patients, as compared to patients with severe congenital neutropenia where long-term high dose G-CSF therapy has been definitively linked to leukemogenesis through the acquisition of CSF3R mutations (Link, et al 2007). In the case of AA, multiple groups found an association between the use and duration of G-CSF therapy and subsequent emergence of monosomy 7 (Desmond, et al 2014, Hama, et al 2015, Kaito, et al 1998, Kojima, et al 2002, Li, et al 2011). A possible mechanistic link was reported by Sloand et al (2006), where pharmacological doses of G-CSF were shown to preferentially stimulate the growth of monosomy 7 clones through abnormal signalling by the GCSF class IV receptor.…”
Section: Clinical Significance Of Clonal Haematopoiesis In Aamentioning
confidence: 99%
“…IST consisting of antithymocyte globulin (ATG) and cyclosporine has proven to be effective in a subset of children with low-grade MDS, with response rate ranging from 30 to 70 % [5,6,14,15,21]. Some patients with chromosomal abnormalities or multilineage dysplasia were also reported to respond to IST [5,6,14,15,21].…”
Section: Management and Treatment Strategymentioning
confidence: 99%
“…Low-grade MDS is diagnosed in all age groups with median age at diagnosis ranging from 6 to 12 years from three representative reports (Table 1) [3,5,6]. Boys and girls are equally affected.…”
Section: Clinical Characteristicsmentioning
confidence: 99%